Threshold analysis of rainfall and groundwater recharge in mitigating drought risks in overexploited groundwater regions - Uneeb Ur Rehman Ali; Jinfeng Du; Muhammad Azram; Hassan Mujtaba Nawaz Saleem; Muhammad Hassan Raza (PLoS ONE, 2026)
This study examines how rainfall and groundwater recharge can help mitigate drought conditions, using the Standardized Precipitation Evapotranspiration Index (SPEI) as the drought indicator. It focuses on the top ten countries experiencing groundwater overexploitation and incorporates a global average perspective to provide deeper insights into these critical relationships. These insights are essential for informed policy-making and integrated decision-making, involving a range of stakeholders from local users to international policymakers on drought mitigation efforts from 1961 to 2022. The analysis employs the novel technique to estimate Dynamic Panel Threshold Regression (DPThR) model. The findings reveal that a 1-millimeter increase in rainfall improves the SPEI by 0.003 units, thereby reducing drought likelihood. The threshold for mitigating drought effects is identified at 614.41 millimeters of annual rainfall, with Pakistan, Iran, and Saudi Arabia being the most at-risk countries when rainfall falls below this level. Conversely, a one-standard-deviation increase in groundwater recharge enhances the SPEI by 5.06 units, indicating a substantial reduction in drought incidence. The threshold for mitigating drought effects is identified at –0.0039 standard deviations, with China, Iran, Mexico, Pakistan, Saudi Arabia, Turkey, and the United States being the most drought-prone when recharge falls below this level. Furthermore, it was found that temperature exerts a consistently negative and highly significant effect, indicating that warming intensifies drought through evapotranspiration and soil moisture depletion. While CO 2 emissions show no significant direct impact. Moreover, the study identifies unidirectional causality running from rainfall, groundwater recharge, temperature, and CO 2 emissions, reinforcing the dominance of hydro-climatic forces in driving drought variability. Policy recommendations include advancing artificial rainfall, enhancing groundwater recharge, and maintaining country-specific water use thresholds to reduce drought risk and strengthen water and climate resilience in overexploited regions.